Study of the principal component analysis in air quality databases (2020)
Technological development has facilitated daily habits, business, the manufacture of large quantities of products, among other types of industrial activities; however, these advances have caused environmental deterioration that seriously threatens the development of society. The increase of greenhouse gases in the atmosphere affects the health of millions of people and is the main factor that has modified the climate on planet Earth. Faced with this situation, it is necessary to carry out actions that allow to quickly adapt to this change and mitigate its effects. The present study proposes the analysis of main components in the data of the pollutant measurements in the city of Bogota, Colombia with the purpose of obtaining a more compact representation of these data, to later apply grouping techniques and obtain factors that allow the emission of an alert for pre-contingency and contingency.